INTERMEDIALITY: TERM, CONCEPTION, METHODOLOGY - Мочернюк, Н. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the specific features of the literary term «intermediality» that is widely used by the Ukrainian scholars have been examined.The author has paid attention to the essentials of its function and the adequacy of using it in particular cases.The origin of the term has been traced.The specific natureof artist-writer’s work analysis in intermediality methodology context has been pointed out in the paper.The range of terms which help to explain the problematic matters of the literature and arts interactions have been established.